Origin of the “People and the Name of the Russian” from the Roxolan Tribe: on the Question of the Existence of Ideas in the Communicative Space of Early New Age - S. V. Sokolov (Научный диалог, 2019)
The question of the origin, functioning and evolution in the historiography of the early New Age of an idea that raises the origin of the Russian people to the Roxolani is considered in the article. Particular attention is paid to the study of the transition of the Roxolan idea from the Italian humanists of the Renaissance through Polish historians of the 16th century to the works of Russian historians of the 18th - early 19th centuries. The author dwells in detail on the argument in favor of the Roxolan concept. It is shown that the historiography of the New Age should be considered as a single communicative space, providing information exchange between historians of different regions. The author comes to the conclusion that in the Roxolan version we are dealing with a powerful intellectual tradition related to the ethnogenetic searches of the early New Age. It is proved that these searches were typical of various national schools of historical writing. The article provides an overview of the work of modern followers of the Roxolan concept and concludes that in these attempts you can see a kind of dialogue with pre-scientific knowledge and a certain inertia of the scientific ideas of the early New Age.